The future of pain research, education, and treatment: a summary of the IOM report “Relieving pain in America: a blueprint for transforming prevention, care, education, and research” - Steglitz, Jeremy (Springer-Verlag, 2012)
The fifth column on Evidence-Based Behavioral Medicine is focused on the Institute of Medicine’s (IOM) report entitled “Relieving Pain in America: A Blueprint for Transforming Prevention, Care, Education, and Research.” The IOM has reported that chronic pain affects 116 million American adults, which is greater than the total of heart disease, cancer, and diabetes combined. It is recommended that data collection takes place at regular intervals using standardized questions, survey protocols, and electronic medical records with the aim of the identifying the following: subpopulations at risk; characteristics of acute and chronic pain; health consequences of pain, including death, disease, and disability; and longitudinal trends of pain. In addition, health education programs should be redesigned to include information about self-management, actions to prevent injuries at the individual and community level, advocacy for pain treatment, and support for improved prevention and control policies. Through teamwork between various professions, from physicians, nurses, and psychologists to physical therapists, pharmacists, and policy makers, advancements in pain awareness, education, research, and treatment should begin to materialize.